2014
DOI: 10.1654/1525-2647-81.2.270
|View full text |Cite
|
Sign up to set email alerts
|

Macroparasites of the Invasive Fish,Cyprinus carpio, in Patagonia, Argentina

Abstract: The ; common carp (Cyprinus carpio L.) is probably the most widely distributed freshwater fish species and is cultured on almost all continents. In South America, studies on the parasites from C. carpio are limited. The aim of the present study was to report on the macroparasites from wild C. carpio populations inhabiting the Neuquen River, which is at the southernmost distribution of C. carpio in Argentina. From spring 2011 to winter 2012, four seasonal samples of C. carpio were collected from the Neuquen Riv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…accumulate mostly in the mesentery and the intestinal serosa of fish but may also reside in the intestinal wall and liver. The genus Contracaecum has a worldwide distribution and includes a range of species which are commonly found in fish serving as paratenic hosts and employ warm-blooded animals (birds, pinnipeds) as final hosts (Mattiucci and Nascetti 2008; Aydogdu et al 2011; Waicheim et al 2014; Corrêa et al 2015; Tavakol et al 2015; Dezfuli et al 2016; Zuo et al 2018). When teleosts are infected by anisakid nematode larvae, they often react by enclosing the worm in a layer of host cells forming a granuloma (Buchmann 2012; Santoro et al 2013; Corrêa et al 2015; Dezfuli et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…accumulate mostly in the mesentery and the intestinal serosa of fish but may also reside in the intestinal wall and liver. The genus Contracaecum has a worldwide distribution and includes a range of species which are commonly found in fish serving as paratenic hosts and employ warm-blooded animals (birds, pinnipeds) as final hosts (Mattiucci and Nascetti 2008; Aydogdu et al 2011; Waicheim et al 2014; Corrêa et al 2015; Tavakol et al 2015; Dezfuli et al 2016; Zuo et al 2018). When teleosts are infected by anisakid nematode larvae, they often react by enclosing the worm in a layer of host cells forming a granuloma (Buchmann 2012; Santoro et al 2013; Corrêa et al 2015; Dezfuli et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its fast colonization to almost all continents and its pathogenicity, B. acheilognathi caused worldwide concern as an important pathogenic and most dangerous fi sh tapeworm, which causes bothriocephalosis of feral but especially of cultured fi sh (Scholz et al, 2012). There are no records of B. acheilognathi published up to date from native fi shes of South America but only two fi ndings from introduced common carps: from Brazil, most probably as a result of the import of carp from Europe (Rego et al, 1999) and from Argentina, found in introduced wild population of Cyprinus carpio (Waicheim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The parasite was introduced into Patagonia probably along with the common carp (Cyprinus carpio, Linnaeus 1758). This fish species has colonized all the Negro River and Neuquén and Limay Rivers near their confluence (Waicheim et al 2014, Crichigno et al 2016 L. cyprinacea was found upstream the dams, where C. carpio is absent, thus it is probable that other small fish species like C. interruptus, Cnesterodon decemmaculatus (Jenyns, 1842), and Jenynsia multidentata (Jenyns, 1842), which are used as bait and for aquarium, are spreading this copepod upstream. In central Argentina, the spread of the copepod is related to the fishing season, when thousands of small fish are sold as bait and transported to different environments (Mancini et al 2008a).…”
Section: Discussionmentioning
confidence: 99%